Penyuluhan Etika Bersosial Media - Sharyanto; Joseph (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2022)
Social Media has become a friend of life for many people. In a day, there are always activities that are made available to open social media, whether for refreshing or indeed looking for information needs. However, from current conditions, the widespread use of social media also often triggers the emergence of deviations caused by the lack of ethics in social media from irresponsible parties. The purpose of this Community Service activity is to provide counseling and understanding about ethics in using social media for the community or members of Karang Taruna RW 17, Pancoran Mas District, Depok City. The method of implementing Community Service activities is a method of counseling and outreach to all members of the RW 17 Youth Organization who want to increase their knowledge of ethics in social media. From the results of this Community Service activity, the participants consisting of members of Karang Taruna RW 17 were very enthusiastic in participating in this social media ethics counseling activity. Through this activity, members of Karang Taruna RW 17 already have an understanding that using social media must be in accordance with applicable ethics and rules.